Humanitarianism and the Global Calls for Volunteerism in the Decade of Action - A Scoping Assessment - Ilesanmi, Oluwatoyin Olatundun (Corpus Intellectual, 2023)
The year 2020 sparked off a decade of value driven and high impact action to deliver the Agenda 2030. However, with less than seven years to go, the efforts being made to advance sustainable solutions to end poverty, reduce inequality, bridge gender gaps, rescue the planet, close the finance gap, and build a peaceful world, are far from the speed or scale required. More so, the onset of the COVID-19 pandemic and other humanitarian disasters across the globe have negatively impacted the gains of SDGs. These have necessitated the need for transformative recovery from the pandemic to reduce risks from future disasters and re-launch the implementation initiative aimed at delivering the global goals and its Agenda during the Decade of Action. Accordingly, the UN calls for the global, local and people-oriented action. The global level action aims at securing effective leadership, resources, and resolutions for implementing the SDGs. The locally oriented action aims at embedding emerging issues into governments, cities and local authorities’ institutional policies, plans, budgets, and regulatory frameworks. The people-oriented action aims at generating coalition of movement among the relevant key stakeholders including nongovernmental organization, civil society organizations (CSOs), the media outfits, private sector, academic community, youth, and among others for advancing the required transformations. Implementation of these three levels of action demands volunteers who will a) create high level movement linking humanitarianism to Global Goals; b) identify risks aimed at ensuring that no one is left behind; c) eradicate extreme poverty; d) act fact to beat the race against climate change (RCC); e) eradicate social injustice and gender inequality, and f) hold leaders to account for the actualization of the SDGs. With less than seven years to go, literature is sparse on the global call for volunteerism during the decade of action. Consequently, this study attempts a review of existing literature on this pertinent issue. The study concludes that volunteerism is one of the veritable tools of intervention in the two distinct fields of operation.